The Volatility of Indonesia Shari’ah Capital Market Stock Price Toward Macro Economics Variable - Malini, Helma; Jais, Mohammad (The Indonesian Capital Market Review, 2014)
Shari’ah stock market is also affected by many highly interrelated economic, social, political and other factor, same as the conventional stock market, the interaction between macroeconomic variables and Shari’ah stock market creating volatility in the stock price as a response towards several shocks. The sensitivity of Shari’ah stock market towards shocks happened related with the future expectation of micro and macro factor in one country which can be predict or unpredictable. There are six macroeconomic variables that used in this research; inflation, exchange rate, interest rate, dow jones index, crude oil palm price, and FED rate. Using vector error correction model (VECM), the result shows that domestic macroeconomic variables that significantly affect Indonesia Shari’ah compliance for long term, while for international macroeconomic variables the selected variable such as FED rate and Dow Jones Index are not significantly affected Indonesia Shari’ah compliance both in short term and long term.